Immune thrombocytopenic purpuera in pregnant women - Rawal, S; Sigdel, MR; Singh, M; Baral, J (Journal of Institute of Medicine Nepal, 2008)
Case report: Immune Thrombocytopenic Purpuera (ITP) is the commonest autoimmune disorder occurring in pregnancy. This is a case of asymptomatic ITP diagnosed in a 21 years primigravida by doing platelet count during routine antenatal investigation at 27th week, who remained refractory to treatment with steroid and platelet transfusion, had to undergo emergency LSCS for low lying placenta, but both the intrapartum and the postpartum period remained uneventful. The baby was assumed to have neonatal alloimmune thrombocytopenia (NAIT) due to low platelet count of 10,000/ cumm and with clinical evidence of petechia on the trunk and hard palate, was later treated with platelet transfusion, intravenous immunoglobulin (IVIG) and steroids. Both the baby and the mother had an uneventful recovery following a multidisciplinary approach with the obstetrician, physician, neonatologist and the anaesthesiologist and both were discharged on steroids on the 10th post operative day. Key Words: Pregnancy, Platelets, ITP The full text of this paper is available at Journal of Institute of Medicine website